Human Reseource Development and Career: Analisa Pengaruh Reward System pada Motivasi dan Disiplin Kinerja Sumber Daya Manusia (SDM) - Resty Agustin; Sopiah; Arief Noviarakhman Zagladi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the influence of the reward system on the motivation and discipline of human resource (HR) performance, as well as its impact on human resource development (HRD) and careers. The method used in this research is a systematic literature review, by collecting ten studies obtained from the Google Scholar and Scopus databases. The analysis results show that a well-designed reward system has an important role in supporting HRD and career development. A reward system that is flexible, achievement-based and responsive to changes in organizational conditions has been proven to strengthen employee motivation and discipline, which in turn improves their performance. In addition, implementing a reward system that rewards innovation, digital skills and knowledge and encourages career renewal has been proven to have a positive impact on the overall competitiveness of the organization. These findings provide insights for organizations in designing and implementing effective reward systems to support sustainable HR and career development.